2008
DOI: 10.1017/s0025100308003277
|View full text |Cite
|
Sign up to set email alerts
|

Typology and acoustic strategies of whistled languages: Phonetic comparison and perceptual cues of whistled vowels

Abstract: Link to this article: http://journals.cambridge.org/abstract_S0025100308003277How to cite this article: Julien Meyer (2008). Typology and acoustic strategies of whistled languages: Phonetic comparison and perceptual cues of whistled vowels.Whistled speech is a complementary natural style of speech to be found in more than thirty languages of the world. This phenomenon, also called 'whistled language', enables distant communication amid the background noise of rural environments. Whistling is used as a sound so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
76
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(82 citation statements)
references
References 27 publications
6
76
0
Order By: Relevance
“…This illustrates how different species have evolved different solutions to the challenge of producing signals that are characterised by a dense spectrum (low F0) and a high amplitude (high G0) with the relatively small larynges of terrestrial mammals. The emergence of whistle languages in several human cultures, where whistling takes over formant-based communication when communicating over long distances in mountainous environments, also provides a very interesting convergence (Classe, 1957;Rialland, 2005;Meyer, 2008). We suggest that further studies should investigate which evolutionary pressures and environmental constraints have led to the emergence of biphonation (e.g.…”
Section: Function and Evolutionmentioning
confidence: 94%
“…This illustrates how different species have evolved different solutions to the challenge of producing signals that are characterised by a dense spectrum (low F0) and a high amplitude (high G0) with the relatively small larynges of terrestrial mammals. The emergence of whistle languages in several human cultures, where whistling takes over formant-based communication when communicating over long distances in mountainous environments, also provides a very interesting convergence (Classe, 1957;Rialland, 2005;Meyer, 2008). We suggest that further studies should investigate which evolutionary pressures and environmental constraints have led to the emergence of biphonation (e.g.…”
Section: Function and Evolutionmentioning
confidence: 94%
“…The acoustic resonance of the whistled signal occurs primarily in the front oral cavities of the reduced vocal tract, which correspond approximately to those that play an important role in defining the upper formants of standard speech (above the 1st formant). This situation is why several previous descriptions have noted that whistled speech signals bear frequency shapes similar in several aspects to the 2nd formant of spoken speech, which occupies a central space in the vocal tract (Busnel and Classe 1976;Rialland 2005;Meyer 2008). Classe (1956) is the first to note that the points of articulation targeted by the tongue during the pronunciation of consonants in Silbo Spanish are similar to those of spoken Spanish.…”
Section: The Case Of Most Non-tonal Languages Formant-based Whistlingmentioning
confidence: 96%
“…In a previous work, we analyzed the frequency distribution of whistled vowels in various non-tonal languages that were recorded during our field inquiry (Meyer 2008). We found that each vowel position is whistled in a definite frequency interval and that each whistled language has its own characteristic frequency distribution of whistled vowels, which is related to how spoken vowels are articulated in each language ( Fig.…”
Section: The Case Of Most Non-tonal Languages Formant-based Whistlingmentioning
confidence: 99%
See 2 more Smart Citations